Artificial pollination and in vitro asymbiotic seed germination in garden orchid Spathoglottis plicata Blume (Orchidaceae) - Thakur, Uma; Dongarwar, Nitin (Recent Research in Science and Technology, 2012)
Pollination biology of Garden orchid Spathoglottis plicata was investigated. Due absence of appropriate pollinator in our area the seed setting was absent or was very low. Artificial pollination (Hand pollination) in S. plicata was studied and seed setting was observed by self and cross pollination. Flowers of S. plicata were pollinated and subsequent capsule development was carefully monitored. Hand pollination of orchid flowers provides an opportunity to discuss floral morphology and associated reproductive biology. Capsules were harvested 60 days after the pollination prior to capsule dehiscence. In vitro asymbiotic germination was 87.3% when seeds were cultured on MS media. The effect of BA and NAA hormones were also observed on seed germination. Seedlings were healthy and stronger when cultured on MS media supplemented with hormones. The cultured seedlings were ready to greenhouse acclimatization after 110 days.